SOCIO-ECONOMIC STATUS OF FISHERS OF RESERVOIRS IN INDIA - EKKA, A.; KATIHA, P. K.; PANDIT, ARUN; BARIK, N.; SALIM, SHYAM; KUMAR, B. GANESH (Journal of the Inland Fisheries Society of India, 2021)
The present study is a rapid assessment of socio-economic status to estimate income, illiteracy and health of reservoir fishers in seven states of India. Structured data from 415 fishermen were collected. The result indicated that against the Indian average literacy rate of 74.52% the literacy rate of 63.32% was recorded among the sampled fishers. The school dropouts were more at secondary level of education (57.75% ). Fishers’ children were vaccinated in most of the states as per the recommendation of Indian Council of Medical Research. The average monthly expenditure of the households was worked out to be Rs. 3148.3 only, which is very low to sustain livelihood; often lead to indebtness. Key words : Socio-economics, reservoir, fishers, income, literacy, health